1984
DOI: 10.1177/004051758405400607
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillation of the Cortex of Merino Wool Fibers by Freezing-Thawing Treatment

Abstract: This work deals with the fibrillation of the cortex of Merino wool by successive freezing (freezing followed by thawing) in various swelling liquids. The freezing- thawing experiments were carried out on native and decuticled wool fibers using water, n-propanol/water, dichloroacetic acid, and formic acid as swelling liquid at freezing temperatures of -78°C and -196°C. The results on native wool showed that the fibers were finely cut in round slices under suitable conditions, but no fi brillation of the cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Mercer reported that such an ortho-para effect could still be observed after cuticle removal [ 19], but in this study, we reexamined the staining behavior using wool fibers completely decuticled by a mild method [ 1,11]. A light micrograph of the decuticled wool fibers dyed with methylene blue is shown in Figure 2, clearly illustrating the bilateral staining.…”
Section: Summary Of Prior Investigatiorimentioning
confidence: 93%
See 4 more Smart Citations
“…Mercer reported that such an ortho-para effect could still be observed after cuticle removal [ 19], but in this study, we reexamined the staining behavior using wool fibers completely decuticled by a mild method [ 1,11]. A light micrograph of the decuticled wool fibers dyed with methylene blue is shown in Figure 2, clearly illustrating the bilateral staining.…”
Section: Summary Of Prior Investigatiorimentioning
confidence: 93%
“…Decuticled wool fibers were prepared by ultrasonic irradiation in aqueous 80% dichloroacetic acid in the same way as reported previously [ 1 ]. Cortical cell particles were prepared according to the procedure of Ito et al [11] ] from decuticled wool fibers by a freezing-thawing treatment in formic acid.…”
Section: Summary Of Prior Investigatiorimentioning
confidence: 99%
See 3 more Smart Citations